Tomato Flu in the Time of COVID-19: Another Challenge for the Indian Health System - Mehta, Vibha; Rahul, J. S.; Shukla, Harsh Vardhan; Pandey, Khushboo (Journal of Laboratory Physicians, 2023)
Just as the country has recently dealt with the increase in COVID-19 and monkey pox cases, another dark cloud of “Tomato flu/ Tomato fever” loomed the skies of the nation. As of 24 august, 2022, 100 kids mainly below the age of 5 have been reported showing symptoms of the flu. Another state of Odisha, suspected similar infectious etiology in 36 cases out of which 26 Children were below the age of 10. This endemic viral illness has triggered an alert to the neighboring states of Tamil Nadu and Karnataka, along with the entire nation at large. The wrath of this disease is not just restricted to India but crossing borders. Tang, et al reported a case of a 13-month-old female child and her 5-year old brother based in United kingdom with similar etiology. Through this report, we aim to alert the frontline pediatricians, who are most likely to come across and manage such daunting cases with these non-specific clinical features in their routine clinical practice across the globe. Early and extreme preventive and surveillance measures must be undertaken to prevent substantial loss in public and private sector
Keywords: COVID 19; Health burden; HFMD; India; Tomato flu